Protective effects of udenafil citrate, piracetam and dexmedetomidine treatment on testicular torsion/detorsion- induced ischaemia/reperfusion injury in rats - Tuglu, D.; Yuvanc, E.; Ozan, T.; Bal, F.; Yilmaz, E.; Atasoy, P.; Batislam, E. (Wiley-Blackwell, 2016)
The aim of this study was to investigate the antioxidant properties of udenafil citrate (1.4 mg kg(-1)-2.8 mg kg(-1)), dexmedetomidine 25 mu g kg(-1) and piracetam 200 mg kg(-1) administered on ipsilateral/contralateral testes after ischaemia in a rat model of testicular torsion/detorsion (T/D) and define its protective effect histologically. Fifty-six Wistar albino rats were included and randomly assigned into 6 groups. No intervention was performed in control group (Group 1, n = 8) and in torsion/detorsion group, (Group 2, n = 8). Udenafil 1.4 mg kg(-1) was given to torsion/detorsion group (Group 3, n = 10), udenafil 2.8 mg kg(-1) was given to torsion/detorsion group (Group 4, n = 10), piracetam 200 mg kg(-1) was given to torsion/detorsion group (Group 5, n = 10) and dexmedetomidine 25 mu g kg(-1) was given to torsion/detorsion group (Group 6, n = 10) intraperitoneally after 60 mins of testicular torsion. Biochemical and histopathological testicular injury were evaluated. When the tissue was examined by TOS values, Group 3, Group 4 and Group 5 were significantly lower than Group 2. In contrary Group 6 values were significantly higher than Group 2. The increasing doses of udenafil demonstrated antioxidant properties on the testis tissue and histopathological that protects the testicles.
Keywords: Dexmedetomidine; piracetam; total antioxidant capacity (TAC); total oxidant status (TOS); udenafil